PREVENTION OF SYMPTOMATIC NEUROMA BY USING SYNTHETIC CONDUITS IN FINGER AMPUTATION STUMPS - ERICK YOSHIO WATAYA; DEBORAH BERNARDO LOPES; DIOGO KENZO TAKAZONO; MARIANA MIRANDA NICOLOSI PESSA; RENATO POLESE RUSIG; LUIZ SORRENTI; LUCIANO RUIZ TORRES; TENG HSIANG WEI; MARCELO ROSA DE REZENDE; RAMES MATTAR JUNIOR (Acta Ortopédica Brasileira)
ABSTRACT Objective: Compare the formation of symptomatic neuromas in patients submitted to digital amputations, with and without nerve conduits (Neurolac® ), and sensitivity return. Methods: Prospective, case-control study, including 14 patients with digital amputations (total of 17 fingers) whose conduits were used on the ulnar or radial side, while the contralateral side was used in the same patients as control. The Tinel test, Semmes-Weinstein monofilament, and two-point discrimination tests were evaluated at one week, two weeks, one month, three months, and six months postoperatively. Results: Using nerve conduits (Neurolac®) in digital nerve amputation stumps had statistical significance (p = 0.04) in preventing pain due to symptomatic neuroma at the end of six months after digital regularization. Conclusion: There is a favorable trend towards using conduits as prophylaxis of symptomatic neuroma formation since the nerves in which they were used showed fewer clinical signs of neuroma formation six months after surgery. Level of evidence II, Prospective comparative study.